Reimagining a path from institutional willingness to readiness: ecosystem variables that promote or impede sustainable transformation in higher education - Whittaker, Joseph A.; Montgomery, Beronda L. (Frontiers in Education, 2025)
Many colleges and universities purport agendas involving strategies centered on the readiness to diversify the faculty, staff, and student bodies, modernize curricula, and promote innovation in research and discovery, among other advancements. However, higher education institutions remain reticent in addressing these variables over the long term and are slow to change. In this article, we argue that impediments to change continue to exist because many conflate willingness to change with readiness for change. We seek to support institutions in identifying and amplifying facilitators—both progressive leaders and stakeholders—who will be supported to assess an institution’s current state and to advocate, facilitate, and help lead the shift to a state of readiness for change to engender improved institutional performance and impact. True commitment to or readiness for change depends on an institution’s ability to accurately conduct a system-wide assessment to identify and safeguard strengths, recognize gaps, and maximize leverage points, i.e., points of likely effective intervention—all of which are necessary to reimagine a progressive and sustainable path forward that would drive an effective redesigning process and the development of system traits to promote meaningful change. Entities that are genuinely committed to change may need to implement interventions or mitigate constraints associated with human capital and personnel (talent identification, support, and retention), economic levers or financial barriers, environmental stewardship, cultural inertia or toxicity, policies and processes, leaders and stakeholders who maintain the status quo or act as gatekeepers, and traditional reward systems. Functional entities within institutions may exist in various disparate states of willingness and readiness, and may progress in a dissonant way, lacking the consensus of effective change-ready leadership. Institutions that can successfully pivot from willingness alone to willingness that facilitates readiness will achieve progressive institutional visions, processes, and implementation. Some may even transition beyond readiness for change to attaining a more dynamic, aspirational position.